Funções do elemento agora em depoimentos de mulheres com pouca ou nenhuma escolarização residentes na comunidade rural de Cubatão-PR - Cerezoli, Jaqueline (2019)
We investigate the speech of illiterate and semi-illiterate women, aged over sixty, who live in the rural community located in the interior of the Paraná coast, called “Comunidade Rural Cubatão”. This locality is part of the municipality of Guaratuba-PR and is geographically located on the border between the states of Santa Catariana and Paraná. The corpus under investigation consists in the occurrences of the element now, recurrent in the speech of the informants. For the composition of the corpus, between 2016 and 2017, semi-structured interviews were conducted, whose script served to stimulate as much as possible spontaneous speech, in order to generate data that could be investigated in the area of Conversation Analysis, following the theoretical-methodological orientation of the Projeto da Norma Urbana Linguística Culta do Brasil (NURC). The analyzes made it possible to verify different functions of the now as evidence of either discursive marker or adverbializing element. Given the analyzes to which the corpus was submitted, it is possible to state that the informants use the now, more clearly, to organize the flow of oral-dialogued text, which basically follows the uses already described in research developed under the NURC. However, uses not yet explored in the consulted works were observed, which may be a sign that in the context of rural area, with the level of schooling on screen, the element now exhibits different functions from those proposed not only by traditionalist grammar studies, but also from other research that focused on the investigation of the element in question. Such functions involve uses that go beyond the operation of the adverbial of time and even typical urban norm uses. It can be affirmed, with the development of this research, that the grammaticalization of the word is linked to multiple functions in the textual organization. It is hoped that this research can help research aimed at analyzing the profile of rural residents, which may point to a description of Portuguese spoken by minorities in the case of oral-dialogued text